The influence of the hydrocarbon cracking system (HCS) on increased torque and reduction of exhaust emissions on a 4-step 1-cylinder gasoline motor - Arif Nur Huda, muhammad; Hadi Susilo, Sugeng; Rohman, Fatkhur; Bin Abas, Mohammad Fadhil (Asian Journal Science and Engineering, 2024)
The automotive industry faces challenges in improving fuel efficiency and reducing exhaust emissions. One solution being developed is the Hydrocarbon Cracking System (HCS), which breaks down hydrocarbon molecules in fuel to enhance combustion efficiency. This study aims to analyze the effects of HCS on engine torque and exhaust emissions (CO, HC, and CO₂) in a four-stroke, single-cylinder gasoline engine. The research method involves an experimental factorial design of 6 × 2, testing torque and exhaust emissions at various engine speeds. Measurements were conducted using a dynamometer and a gas analyzer to compare standard conditions with HCS implementation. The results indicate that HCS increases engine torque by 3.40% and reduces CO and HC emissions by 28.12% and 54.35%, respectively. However, CO₂ emissions increased by 12.48%, indicating more complete combustion. Overall, HCS proves to enhance engine efficiency and reduce harmful emissions, making it a potential eco-friendly solution for motor vehicles.